Pharmaceutical potential of quantum dots. (31st October 2018) - Jha, Swati; Mathur, Prateek; Ramteke, Suman; Jain, Narendra Kumar
Abstract: Quantum dots (QDs) or fluorescent nanocrystals are designed nanoparticles that are promising for several biological and bio-medical applications as well as drug delivery and simultaneous cellular imaging. QD's have exhibited promising potential primarily in receptor based targeting as a result of their distinctive physicochemical properties. Functionalized QDs (f-QDs) have been developed as effective, safe, nano-sized smart systems to deliver a wide range of bio-actives. Surface modified fluorescent carbon QDs with surface modification have attracted attention as targeting ligand to accomplish cellular targeting with enhanced specificity. Several surface engineered and conjugated fluorescent carbon QDs are presently being explored for the treatment of cancer and the outcome is eagerly awaited.